1999
DOI: 10.5465/amr.1999.2202131
|View full text |Cite
|
Sign up to set email alerts
|

Tit for Tat? The Spiraling Effect of Incivility in the Workplace

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

72
2,395
3
63

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,989 publications
(2,533 citation statements)
references
References 58 publications
72
2,395
3
63
Order By: Relevance
“…The increasing attention to incivility in the workplace is reflected in a rapidly growing scientific literature (e.g., Andersson & Pearson, 1999;Cortina & Magley, 2009;Cortina, Magley, Williams, & Langhout, 2001;Giumetti et al, 2013;Lim & Cortina, 2005;Lim, Cortina, & Magley, 2008;Lim & Teo, 2009;Martin & Hine, 2005;Pearson, Andersson, & Wegner, 2001). Workplace incivility, generally taken to be rude and discourteous behavior that demonstrates a lack of regard for others, has been defined as ''lowintensity deviant behavior with ambiguous intent to harm the target, in violation of workplace norms for mutual respect'' (Andersson & Pearson, 1999, p. 457).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increasing attention to incivility in the workplace is reflected in a rapidly growing scientific literature (e.g., Andersson & Pearson, 1999;Cortina & Magley, 2009;Cortina, Magley, Williams, & Langhout, 2001;Giumetti et al, 2013;Lim & Cortina, 2005;Lim, Cortina, & Magley, 2008;Lim & Teo, 2009;Martin & Hine, 2005;Pearson, Andersson, & Wegner, 2001). Workplace incivility, generally taken to be rude and discourteous behavior that demonstrates a lack of regard for others, has been defined as ''lowintensity deviant behavior with ambiguous intent to harm the target, in violation of workplace norms for mutual respect'' (Andersson & Pearson, 1999, p. 457).…”
Section: Introductionmentioning
confidence: 98%
“…However, one might also ask how often employees experience workplace incivility. Incivility is defined as norm deviant behavior (Andersson & Pearson, 1999) and it is telling to consider the frequency with which employees report incivility in their workplaces. As noted above, in Cortina et al's (2001) study, 71% of employees experienced incivility over a five year time frame, but most reported that they experienced those uncivil actions an average of only once or twice (39%) or sometimes (25%) over the five year period.…”
Section: Introductionmentioning
confidence: 99%
“…Intervening in an incident of workplace mistreatment could make observers more likely to be targeted for mistreatment themselves (e.g., a secondary spiral of incivility; Andersson & Pearson, 1999). It is also possible that observer intervention could exacerbate the negative outcomes of incivility for the target, as it may draw attention to a situation that the target would prefer to minimize.…”
Section: Our Findings Have Important Theoretical and Practical Implicmentioning
confidence: 99%
“…However, such forms of "vigilante" justice can be counterproductive, because they may cause incivility to spread and escalate (Andersson & Pearson, 1999). Therefore, in this paper, we consider other forms of third-party responding, including constructive interventions to stop the incivility, the choice to avoid the perpetrator and opt for non-response, and "invisible remedies" of supporting the target (e.g., Rosette, Carton, Bowes-Sperry, & Hewlin, 2013).…”
Section: Witnessing Wrongdoing: the Effects Of Observer Power On Incimentioning
confidence: 99%
See 1 more Smart Citation